A review on valorization of different byproducts of mango (Mangifera indica L.) for functional food and human health. (August 2022) - Gupta, Alok Kumar; Gurjar, Pawan Singh; Beer, Karma; Pongener, Alemwati; Ravi, S.C.; Singh, Smita; Verma, Anil; Singh, Abha; Thakur, Mamta; Tripathy, Soubhagya; Verma, Deepak Kumar
Abstract: Mango ( Mangifera indica ) is one of the most popular fruits in the world. During processing, the byproducts such as peel, seed and kernel are produced, which are high in bioactive components. There is a need to utilize them to formulate food products or extract the functional components. This paper provides an overview about the nutritional composition of mango byproducts besides discussing the bioactive compounds (BACs). The manuscript also explores the existing evidences on the biological activity of BACs and the potential of mango peel and seed kernel to develop value-added foods and beverages. Mango kernel is a great source of macronutrients and micronutrients with a relatively high antioxidant and polyphenolic content, whereas mango peels are rich in protocatechuic acids, mangiferin and β-carotene. These BACs demonstrate numerous biological activities including anti-oxidant antimicrobial, anti-diabetic, anti-cancer and anti-inflammatory properties. One of the promising strategies to utilize these byproducts is the development of different value-added food products such as bakery products, meat products, and dairy-based products for improving their phenolic compounds, fiber content, carotenoids, and antioxidant activity. This review thus illustrates the nutraceutical and pharmacological properties of mango byproducts and their appropriate use to enhance nutrition and health. Graphical abstract: Image 1 Highlights: Mango by-products (peel, seed & seed husk) constitute 35–60% of the fruit. They are rich in bioactive compounds (BACs) like fibre, mangiferin, β-carotene, etc. These BACs exhibits biological activities and offer physiological benefits. Recent methods of BACs extraction, identification and quantification are discussed. Extracted BACs are employed as antioxidants, anticancer, antibiotics, and antibacterial agents. Mango by-products show huge potential to develop value-added food products.